Transcutaneous billirubinometry to estimate total serum bilirubin in neonatal jaundice - Andra Kurnianto; Herman Bermawi; Afifa Darmawanti; Erial Bahar (Indonesian Pediatric Society Publishing House, 2017)
Background The gold standard for diagnosis of neonatal jaundice is total serum bilirubin (TSB) measurement. This method, however, is invasive, painful, and costly in terms of workload, time, and money. Moreover, repeated blood sampling may lead to significant blood loss, which is of particular concern in preterm infants. To overcome these drawbacks, non-invasive methods of bilirubin measurement have been proposed. Transcutaneous bilirubinometry (TcB) determines the yellowness of the subcutaneous tissue of a newborn infant by measuring the difference between optical densities for light in the blue and green wavelength regions. Objective To evaluate the accuracy of transcutaneous bilirubinometry for estimating TSB levels in neonatal jaundice. Methods Subjects were infants aged < 28 days with jaundice who had never been treated with phototherapy or exchange transfusion. The study was done from February to July 2016 in Mohammad Hoesin Hospital. Subjects underwent transcutaneous bilirubin (TcB) and TSB assays, with a maximum interval of 15 minutes between tests. Results One hundred fifty patients were included in this study. The TcB values > 5 mg/dL were correlated to TSB > 5 mg/dL, with 100% sensitivity and 83.3% specificity. This cut-off point was obtained from a receiver-operator characteristic (ROC) curve with AUC 99.3% (95%CI 97.9 to 100%; P< 0.001).The correlation coefficients (r) for TSB and TcB measurements on the forehead were 0.897 (P<0.001). Conclusion Transcutaneous bilirubinometry can be used to accurately estimate TSB levels in neonatal jaundice, and may be useful in clinical practice as a non-invasive method to reduce blood sampling.